Peritoneal Dialysis Drop-out: Causes and Prevention Strategies - Kunal Chaudhary (International Journal of Nephrology)
Peritoneal dialysis (PD) as a renal replacement therapy (RRT) has become wide spread since its inception more than twenty-five years back. Since then, several advances have been made and PD has been accepted as an alternative therapy to hemodialysis (HD), with excellent survival, lower cost, and improved quality of life. In spite of comparable survival of HD and PD, improved PD techniques over the last few years, and lower health care costs with PD, PD prevalence remains low in many countries. An important reason for the low PD prevalence is patient dropouts, that is, transfer to HD. The reasons for dropouts are multifactorial, that is, modality related, system related, and patient related. These include episodes of peritonitis, catheter-related problems, ultrafiltration failure, patient fatigue, and provider comfort. This review discusses the various factors that contribute to PD dropout and the strategies to prevent it.